Composite cooling material
The composite cooling material addresses attachment issues by using a magnetic layer and a resin layer with high solar reflectance and emissivity, enhancing usability and cooling efficiency on metal surfaces.
Patent Information
- Application Number
- JP2023112666
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2043-07-07
AI Technical Summary
Conventional composite cooling materials face challenges in ease of attachment to metal surfaces, particularly when a protective layer made of acrylic resin is used, leading to difficulties in adhering them to metal plates.
Incorporating a magnetic material layer with a cooling layer that has a solar reflectance of 80% or more, allowing magnetic attachment to metal surfaces, and utilizing a resin material layer with specific optical properties to enhance emissivity and reflectivity for effective radiative cooling.
The composite cooling material achieves improved usability and effective radiative cooling by magnetically attaching to metal surfaces, reflecting sunlight, and efficiently emitting thermal radiation, even in daytime solar radiation environments.
Smart Images

Figure 2025010556000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite cooling material that has the function of cooling the reverse side of a material. [Background technology]
[0002] Radiative cooling is known as a function for cooling the reverse side of a material. Radiative cooling is a phenomenon in which a material's temperature drops when it radiates electromagnetic waves such as infrared rays to its surroundings. By utilizing this phenomenon, it is possible to create a composite cooling material (composite cooling device) that cools an object without consuming energy such as electricity.
[0003] A conventional example of a composite cooling material (composite cooling device) is one that is configured by stacking an infrared emitting layer that emits infrared light from a emitting surface and a light reflecting layer that is positioned on the opposite side of the infrared emitting layer to the side where the emitting surface is present (see, for example, Patent Document 1).
[0004] In other words, the composite cooling material (composite cooling device) has an infrared radiation layer that emits a large amount of thermal radiation energy in the wavelength range from 8 μm to 14 μm, and the light reflective layer reflects the light (ultraviolet light, visible light, infrared light) that passes through the infrared radiation layer and radiates it from the radiating surface, thereby preventing the object to be cooled from heating up, and can cool the object to be cooled even in a daytime solar environment.
[0005] Incidentally, the light reflecting layer has the effect of reflecting, toward the infrared radiation layer, in addition to the light that has transmitted through the infrared radiation layer, light that is emitted from the infrared radiation layer toward the side where the light reflecting layer is present. However, in the following description, it will be described that the purpose of providing the light reflecting layer is to reflect light (ultraviolet light, visible light, infrared light) that has transmitted through the infrared radiation layer. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 2018-526599 Summary of the Invention [Problem to be solved by the invention]
[0007] As an example of the use of the composite cooling material, it may be desirable to attach (mount) it with an adhesive or pressure-sensitive adhesive to the outer surface of a metal plate (e.g., made of metal such as iron, iron alloy, steel plate, etc.), such as the outer surface of an automobile or the outer surface of a container. In such a case, the layer located on the rear side of the composite cooling material, for example, the separation-side protective layer, is used for connection to the mounting object. In other words, the separation-side protective layer is attached to the outer surface of the metal plate-shaped body with an adhesive or a pressure-sensitive adhesive.
[0008] However, when the separating side protective layer is made of acrylic resin, it becomes impossible to properly attach the separating side protective layer to the metal plate-like body with adhesive, and conventional composite cooling materials can be difficult to use, so improvement is desired.
[0009] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a composite cooling material that can improve usability. [Means for solving the problem]
[0010] The characteristic configuration of the composite cooling material to achieve the above object is as follows: a magnetic material layer including a magnetic material; a cooling layer provided on an outer surface of the magnetic material layer; The cooling layer has a first optical characteristic of having a solar reflectance of 80% or more.
[0011] According to this configuration, the cooling layer has the first optical property of a solar reflectance of 80% or more, and therefore can satisfactorily exhibit a predetermined solar reflecting function.
[0012] Furthermore, with the composite cooling material of this configuration, a magnetic material layer is provided on the back side opposite the outer surface of the cooling layer, which can be attached to the metal plate-like object to be attached by magnetic force, so that the composite cooling material can be attached to the object to be attached. That is, by appropriately selecting a metal plate-like body as the attachment object that can be attached by the magnetic force generated by the magnetic material layer, the composite cooling material can be attached satisfactorily to the plate-like body. In short, the characteristic configuration of the composite cooling material can improve usability.
[0013] Further characteristic features of the composite cooling material are: the cooling layer is configured to include an infrared emitting layer that emits infrared light from a radiation surface, and a light reflecting layer located on the infrared emitting layer opposite to the side on which the radiation surface is present, and has a second optical characteristic in which an average emissivity, which is a wavelength average of the emissivity of infrared light of 8 μm or more and 14 μm or less, is 80% or more; the infrared radiation layer is a resin material layer made of a vinyl chloride resin or a vinylidene chloride resin and has a thickness adjusted to emit thermal radiation energy in a wavelength band of 8 μm to 14 μm that is greater than the absorbed solar light energy; the light reflective layer comprises silver or a silver alloy; The cooling layer and the magnetic material layer are connected by a connecting layer containing one or more of vinyl chloride resin, vinylidene chloride resin, polyolefin resin, polyester resin, acrylic resin, urethane resin, silicone resin, and rubber resin.
[0014] Sunlight incident from the emitting layer of the infrared emitting layer in the cooling layer passes through the resin material layer, is reflected by the light reflecting layer located on the opposite side to the side where the emitting surface of the resin material layer is present, and is allowed to escape from the system through the emitting surface. In the description of this specification, when simply referring to light, the concept of light includes ultraviolet light (ultraviolet light), visible light, and infrared light. When these are described in terms of the wavelength of light as electromagnetic waves, they include electromagnetic waves with wavelengths of 10 nm to 20,000 nm (electromagnetic waves of 0.01 μm to 20 μm).
[0015] In addition, the heat transferred (heat input) to the cooling layer is converted into infrared rays in the resin material layer acting as the infrared radiation layer, and is released to the outside of the system from the radiation surface. In this way, the cooling layer reflects the sunlight irradiated onto it, and can also radiate heat transferred to the cooling layer (e.g., heat transferred from the atmosphere or from the film material cooled by the cooling layer) outside the system as infrared light.
[0016] In addition, the cooling layer has a second optical characteristic of an average emissivity of 80% or more, which is the wavelength average of the emissivity of infrared light from 8 μm to 14 μm, and the resin material layer is adjusted to a thickness such that it emits thermal radiation energy in the wavelength range from 8 μm to 14 μm that is greater than the absorbed solar energy.Therefore, the cooling function can be exerted even in a daytime solar environment while the light reflective layer comprising silver or a silver alloy appropriately reflects solar light.
[0017] Therefore, even in a daytime solar radiation environment, the cooling layer can cool the region inside the cooling layer (the side where the magnetic material layer exists) by radiative cooling.
[0018] Thin film vinyl chloride resin or vinylidene chloride resin becomes soft by adding a plasticizer, and when it comes into contact with other objects, it can flexibly change shape to match the object, avoiding damage and allowing it to be maintained in a beautiful condition for a long period of time.Incidentally, thin film fluororesin is hard, so it cannot flexibly change shape when it comes into contact with other objects, is easily damaged, and is difficult to maintain in a beautiful condition. Furthermore, by adding a plasticizer to polyvinyl chloride resin, even if it is scratched, it can be deformed by heating it to 80°C or higher, and the surface scratches can be removed and smoothed out, meaning that the scratches can be repaired by itself. Fluorine resin and silicone rubber do not have this characteristic. This characteristic of soft polyvinyl chloride resin allows it to maintain a clean state for a long period of time. This leads to the maintenance of radiative cooling performance over a long period of time. Furthermore, since vinyl chloride resins are flame retardant and difficult to biodegrade, they are suitable as resin materials for forming the resin material layers of radiative cooling devices used outdoors. The vinyl chloride resin used in the present invention is a homopolymer of vinyl chloride or vinylidene chloride or a copolymer of vinyl chloride or vinylidene chloride, and the production method thereof is carried out by a conventionally known polymerization method.
[0019] In addition, the thin film of polyvinyl chloride resin is flexible, and since a plasticizer is mixed into the polyvinyl chloride resin to soften it, the resin material layer becomes even more flexible, and as a result, the radiative cooling device becomes flexible.
[0020] In addition, as in this configuration, by connecting the cooling layer and the magnetic material layer with a connecting layer containing one or more of vinyl chloride resin, vinylidene chloride resin, polyolefin resin, acrylic resin, urethane resin, silicone resin, and rubber resin, the cooling layer and the magnetic material layer can be well connected.
[0021] Further characteristic features of the composite cooling material are: The connection layer contains at least one of vinyl chloride resin and polyolefin resin.
[0022] According to this configuration, by forming the connection layer that connects the cooling layer and the magnetic material layer from at least one of vinyl chloride resin and polyolefin resin, the cooling layer and the magnetic material layer can be connected even better.
[0023] Further characteristic features of the composite cooling material are: The magnetic material layer contains at least ferrite and a binder resin, and has a thickness of 0.2 mm to 2.0 mm.
[0024] As in this configuration, the magnetic material layer can be made of a material containing at least ferrite and a binder resin. In particular, by making the thickness of the magnetic material layer 0.2 mm or more, the magnetic force acting as a mounting force for the metal plate-like body to be attached can be exhibited well, and long-term adhesion stability can be improved. In addition, by making the thickness 2.0 mm or less, even if a heat source is present on the back side of the composite cooling material, the heat dissipation from the back side to the outer surface side can be maintained at a constant level or higher.
[0025] Further characteristic features of the composite cooling material are: the cooling layer includes an infrared emitting layer that emits infrared light from an emitting surface; The infrared radiation layer has a plurality of granular light reflecting portions that reflect light.
[0026] According to this configuration, the infrared radiation layer of the cooling layer is provided with a plurality of granular light-reflecting portions that reflect light. For example, by providing a sufficient number of such granular light-reflecting portions in the infrared radiation layer, the infrared radiation layer itself as a radiation layer can also have the function of a light-reflecting layer that reflects light. In some cases, this eliminates the need to separately provide a light-reflecting layer made of a metal such as silver or a silver alloy, thereby enabling costs to be reduced.
[0027] Even if the composite cooling layer is configured to include an infrared radiation layer that emits infrared light as well as a light reflection layer that reflects light, by providing the infrared radiation layer with a plurality of granular light reflection portions, light is reflected (solar radiation is reflected) not only by the light reflection layer but also by the light reflection portions of the infrared radiation layer, so that better cooling function can be achieved when the solar radiation is strong.
[0028] Furthermore, according to this configuration, even if the silver or silver alloy in the light reflecting layer breaks and cracks when attaching the composite cooling material to an object, the light can be reflected by the light reflecting portion of the infrared radiation layer, thereby preventing a decrease in cooling performance.
[0029] In the composite cooling material described above, it is preferable that the particle size of the light reflecting portion is 1 nm or more and 300 μm or less.
[0030] Furthermore, in the composite cooling materials explained so far, The light reflecting portion is preferably porous.
[0031] Furthermore, in the composite cooling materials explained so far, The light reflecting portion includes at least one of an inorganic filler and an organic filler, The inorganic filler includes at least one of glass microbeads, ceramic microbeads, silicon oxide particles, silicon carbide particles, silicon nitride particles, barium sulfate particles, and calcium carbonate particles; The organic filler suitably contains at least one type of polymer having any one of the functional groups CO, C-Cl, CF, CN, C-Si, and Si-O.
[0032] In the composite cooling materials explained so far, The cooling layer includes an inorganic filler, The inorganic filler suitably contains at least one of glass microbeads, ceramic microbeads, silicon oxide particles, silicon carbide particles, silicon nitride particles, barium sulfate particles, and calcium carbonate particles.
[0033] Further characteristic features of the composite cooling material are: The thickness of the resin material layer is The thickness is adjusted to provide light absorption characteristics such that the wavelength average light absorptance for wavelengths from 0.4 μm to 0.5 μm is 13% or less, the wavelength average light absorptance for wavelengths from 0.5 μm to 0.8 μm is 4% or less, the wavelength average light absorptance for wavelengths from 0.8 μm to 1.5 μm is within 1%, and the wavelength average light absorptance for wavelengths from 1.5 μm to 2.5 μm is 40% or less.
[0034] The wavelength average of the light absorptance at wavelengths of 0.4 μm to 0.5 μm means the average value of the light absorptance for each wavelength in the range of 0.4 μm to 0.5 μm, and the same applies to the wavelength average of the light absorptance at wavelengths of 0.5 μm to 0.8 μm, the wavelength average of the light absorptance at wavelengths of 0.8 μm to 1.5 μm, and the wavelength average of the light absorptance at wavelengths of 1.5 μm to 2.5 μm. Other similar descriptions including emissivity also mean similar average values, and the same applies hereinafter in this specification.
[0035] That is, the light absorptivity and emissivity (light emissivity) of the resin material layer change depending on the thickness. Therefore, it is necessary to adjust the thickness of the resin material layer so that it absorbs as little sunlight as possible and emits large thermal radiation in the wavelength band of the so-called atmospheric window region (the region of light wavelengths from 8 μm to 20 μm).
[0036] Specifically, in terms of the light absorptance (light absorption characteristics) of sunlight in the resin material layer, the wavelength average light absorptance of 0.4 μm to 0.5 μm wavelengths must be 13% or less, the wavelength average light absorptance of 0.5 μm to 0.8 μm wavelengths must be 4% or less, the wavelength average light absorptance of 0.8 μm to 1.5 μm wavelengths must be within 1%, and the wavelength average light absorptance of 1.5 μm to 2.5 μm must be 40% or less. Note that for the light absorptance of 2.5 μm to 4 μm, the wavelength average must be 100% or less. When the light absorptance is distributed in this way, the light absorptance of sunlight is 10% or less, which corresponds to 100 W or less in terms of energy.
[0037] In other words, the light absorption rate of sunlight increases as the thickness of the resin material layer increases. When the resin material layer is made thick, the emissivity of the atmospheric window becomes almost 1, and the thermal radiation emitted into space is 125 W / m 2 from 160 W / m 2 It becomes. The solar absorption in the light reflecting layer is 50W / m 2 It is preferable that: Therefore, the sum of the solar light absorption in the resin material layer and the light reflective layer is 150 W / m 2 As described above, it is preferable to use a resin material layer having a small absorptance near the peak value of the solar spectrum.
[0038] Furthermore, in terms of the emissivity (thermal radiation characteristics) of the resin material layer that radiates infrared light, the wavelength average of the emissivity in the wavelength range from 8 μm to 14 μm must be 40% or more. That is, 50 W / m absorbed by the light reflecting layer 2In order to emit the same amount of thermal radiation as sunlight from a resin material layer into space, the resin material layer needs to emit more thermal radiation than that. For example, when the outside temperature is 30°C, the maximum thermal radiation of the atmospheric window with wavelengths from 8 μm to 14 μm is 200 W / m 2 (Calculated with an emissivity of 1). This value can be obtained on a clear day in a dry environment with thin air, such as a high mountain. Since the atmosphere is thicker in lowlands than in high mountains, the wavelength band of the atmospheric window is narrower and the transmittance is lower. Incidentally, this is called the "atmospheric window becoming narrower."
[0039] In addition, the environment in which the composite cooling material is actually used may be humid, in which case the atmospheric window is also narrow. When used in low altitudes, the thermal radiation generated in the atmospheric window area is 160 W / m at 30°C under good conditions. 2 (calculated assuming emissivity of 1). In addition, when there is haze or smog in the sky, as is common in Japan, the atmospheric window becomes even narrower and radiation into space is reduced to 125 W / m 2 It will be about that amount.
[0040] In consideration of this situation, the wavelength average of the emissivity from 8 μm to 14 μm is set to 40% or more (thermal radiation intensity in the atmospheric window band is 50 W / m 2 Unless the temperature is above 100°C, it cannot be used in low altitude areas of the mid-latitudes. Therefore, by adjusting the thickness of the resin material layer so that it falls within the above-mentioned optical specification range, the heat output at the atmospheric window becomes greater than the heat input due to the absorption of sunlight, making it possible to achieve radiative cooling outdoors even in a daytime solar radiation environment. That is, when the resin material layer is formed of vinyl chloride resin or vinylidene chloride resin, the thickness of the resin material layer is preferably 100 μm or less and 10 μm or more.
[0041] In short, according to a further characteristic configuration of the composite cooling material, the heat output at the atmospheric window is greater than the heat input due to the absorption of sunlight, making it possible to perform radiative cooling outdoors even in a solar radiation environment.
[0042] Further characteristic features of the composite cooling material are: The light reflective layer has a reflectance of 90% or more for wavelengths of 0.4 μm to 0.5 μm, and a reflectance of 96% or more for wavelengths longer than 0.5 μm.
[0043] That is, the solar spectrum exists from wavelength 0.295 μm to 4 μm, and the intensity increases as the wavelength increases from 0.4 μm, and the intensity is particularly high from wavelength 0.5 μm to wavelength 2.5 μm. If the light-reflecting layer has reflective characteristics that show a reflectance of 90% or more from 0.4 μm to 0.5 μm wavelengths and a reflectance of 96% or more at wavelengths longer than 0.5 μm, the light-reflecting layer will only absorb about 5% or less of the solar energy.
[0044] As a result, the solar energy absorbed by the light-reflecting layer at noon in summer was reduced to 50 W / m 2 The thickness can be set to about 100 μm or less, and radiation cooling by the resin material layer can be performed satisfactorily. In this specification, unless otherwise specified, the spectrum of sunlight is in accordance with the AM1.5G standard.
[0045] In short, according to a further characteristic configuration of the composite cooling material, the absorption of solar energy by the light reflecting layer can be suppressed, and radiative cooling by the resin material layer can be performed effectively.
[0046] Further characteristic features of the composite cooling material are: The light reflecting layer has a thickness of 50 nm or more.
[0047] In other words, in order for the light reflecting layer to have the above-mentioned reflectance characteristics, i.e., a reflectance of 90% or more at wavelengths from 0.4 μm to 0.5 μm and a reflectance of 96% or more at wavelengths longer than 0.5 μm, the reflective material on the radiation surface side of the light reflecting layer needs to be silver or a silver alloy, as described above. In the case where a light reflective layer made of only silver or a silver alloy is used to reflect sunlight while providing the above-mentioned reflectance characteristics, as in the above-mentioned characteristic configuration, a thickness of 50 nm or more is required.
[0048] In short, according to a further characteristic configuration of the composite cooling material of the present invention, the absorption of solar energy by the light reflecting layer can be appropriately suppressed, and radiative cooling by the resin material layer can be performed effectively.
[0049] Further characteristic features of the composite cooling material are: The light reflecting layer has a laminated structure of silver or a silver alloy located closer to the resin material layer and aluminum or an aluminum alloy located away from the resin material layer.
[0050] That is, to give the light reflecting layer the above-mentioned reflectance characteristics, it may be a structure in which silver or silver alloy and aluminum or aluminum alloy are laminated. Note that in this case, the reflective material on the emitting surface side must be silver or silver alloy. In this case, the thickness of the silver must be 10 nm or more, and the thickness of the aluminum must be 30 nm or more.
[0051] Furthermore, since aluminum or an aluminum alloy is less expensive than silver or a silver alloy, it is possible to reduce the cost of the light reflective layer while still providing appropriate reflectance characteristics. In other words, by making the expensive silver or silver alloy thinner, the cost of the light reflective layer can be reduced, but by making the light reflective layer a laminated structure of silver or silver alloy and aluminum or aluminum alloy, it is possible to provide the light reflective layer with appropriate reflectance characteristics and reduce the cost.
[0052] In short, this further characteristic configuration of the composite cooling material allows the light reflective layer to be made inexpensively while still providing suitable reflectance characteristics. [Brief description of the drawings]
[0053] [Figure 1] FIG. 1 is a diagram illustrating the basic configuration of a composite cooling material. [Diagram 2] FIG. 4 is a diagram showing the relationship between the light absorptance of a resin material and the wavelength. [Diagram 3] FIG. 1 is a diagram showing the emissivity spectrum of polyvinyl chloride resin. [Figure 4]FIG. 2 is a diagram showing the emissivity spectrum of vinylidene chloride resin. [Diagram 5] FIG. 2 shows the light reflectance spectrum of a silver-based light reflective layer. [Figure 6] FIG. 1 is a diagram showing a specific configuration of a composite cooling material. [Figure 7] FIG. 1 is a diagram showing a specific configuration of a composite cooling material. [Figure 8] FIG. 1 is a diagram showing a specific configuration of a composite cooling material. [Figure 9] FIG. 1 is a diagram showing a specific configuration of a composite cooling material. [Figure 10] FIG. 1 is a graph showing the relationship between light transmittance and wavelength of polyethylene. [Figure 11] FIG. 1 is a diagram illustrating a test configuration. [Figure 12] FIG. 13 is a diagram showing test results when the protective layer is made of polyethylene. [Figure 13] FIG. 13 is a diagram showing test results when the protective layer is made of ultraviolet absorbing acrylic. [Figure 14] FIG. 2 is a diagram showing the emissivity spectrum of polyethylene. [Figure 15] FIG. 1 is a diagram showing experimental results of a plasticizer mixed into a polyvinyl chloride resin. [Figure 16] FIG. 13 is a diagram illustrating another configuration of the cooling layer. [Figure 17] FIG. 13 is a diagram showing a configuration in which a cooling layer is formed in an uneven shape. [Figure 18] FIG. 13 is a diagram showing a specific example of an uneven cooling layer. [Figure 19] FIG. 13 is a diagram showing a specific example of an uneven cooling layer. [Figure 20] 13A and 13B are diagrams illustrating a configuration in which a resin material layer is provided with a light reflecting portion. [Figure 21] 13A and 13B are diagrams illustrating a configuration in which a resin material layer is provided with a light reflecting portion. [Figure 22] FIG. 13 is a diagram illustrating a configuration in which a glue layer is provided with a light reflecting portion. [Figure 23] FIG. 13 is a diagram illustrating a configuration in which a glue layer is provided with a light reflecting portion. [Figure 24] 13 is a graph showing experimental results. [Diagram 25] 13A and 13B are diagrams illustrating a configuration in which the front and back surfaces of a resin material layer are uneven. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0054] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. [Basic composition of composite cooling material] As shown in Fig. 1, the composite cooling material W is configured such that a film-like cooling layer CP is connected (adhered) to the outer surface of a magnetic material layer E containing a magnetic material having magnetic force, and the back side (lower side in Fig. 1: the side of the magnetic material layer E opposite to the side where the cooling layer CP exists) of the magnetic material layer E is cooled by the radiative cooling action of the cooling layer CP. In Fig. 1, the cooling layer CP is connected to the outer surface of the magnetic material layer E by a connecting layer S made of a resin, which will be described later.
[0055] 1 illustrates an example in which a composite cooling material W is attached to a warehouse 1 having a roof and side parts made of metal plates. That is, a plurality of composite cooling materials W are attached to the roof and surrounding side parts of the warehouse 1. Note that, as the metal plate-like body to be attached, iron, iron alloy, steel plate, etc. are suitable as materials that can be attached by magnetic force generated by magnetic materials.
[0056] The cooling layer CP is formed in a film shape and includes a laminated structure of an infrared radiation layer A that emits infrared light IR from a radiation surface H, a light reflecting layer B that is located on the side of the infrared radiation layer A opposite to the side on which the radiation surface H exists, and a protective layer D between the infrared radiation layer A and the light reflecting layer B. That is, the cooling layer CP is configured as a radiative cooling film. The cooling layer CP has a first optical characteristic of a solar reflectance of 80% or more and a second optical characteristic of an average emissivity, which is the wavelength average of the emissivity of infrared light of 8 μm or more and 14 μm or less, of 80% or more.
[0057] The light-reflecting layer B reflects light L, such as sunlight, that has passed through the infrared-emitting layer A and the protective layer D, and its reflection characteristics are a reflectance of 90% or more at wavelengths of 400 nm to 500 nm and a reflectance of 96% or more at wavelengths longer than 500 nm. The solar spectrum exists in the wavelength range from 300 nm to 4000 nm, and the intensity increases as the wavelength increases from 400 nm, and is particularly strong in the wavelength range from 500 nm to 1800 nm.
[0058] In this embodiment, the light L includes ultraviolet light (ultraviolet light), visible light, and infrared light, and when these are described in terms of the wavelength of light as electromagnetic waves, they include electromagnetic waves with wavelengths of 10 nm to 20,000 nm (electromagnetic waves of 0.01 μm to 20 μm). Incidentally, in this document, the wavelength range of ultraviolet light (ultraviolet light) is between 295 nm and 400 nm.
[0059] Since the light-reflecting layer B exhibits a reflectance of 90% or more from 400 nm to 500 nm and a reflectance of 96% or more for wavelengths longer than 500 nm, the solar energy absorbed by the cooling layer CP (radiative cooling film) in the light-reflecting layer B can be reduced to 5% or less. In other words, the solar energy absorbed at noon in summer can be reduced to about 50 W.
[0060] The light-reflecting layer B is composed of silver or a silver alloy, or is composed of a laminated structure of silver or a silver alloy located adjacent to the protective layer D and aluminum or an aluminum alloy located away from the protective layer D, and is flexible, as will be described in more detail below.
[0061] The infrared radiation layer A is configured as a resin material layer J made of polyvinyl chloride resin or vinylidene chloride resin whose thickness is adjusted so that it emits thermal radiation energy in the wavelength range from 8 μm to 14 μm that is greater than the absorbed solar energy, and details of which will be described later.
[0062] Therefore, the cooling layer CP is configured to reflect a portion of the light L incident on the cooling layer CP at the radiation surface H of the infrared radiation layer A, and to reflect the light (sunlight, etc.) that is transmitted through the resin material layer J and the protective layer D from the light incident on the cooling layer CP at the light reflecting layer B and allow it to escape to the outside from the radiation surface H.
[0063] The heat input to the cooling layer CP from the magnetic material layer E, which is located on the opposite side of the light-reflecting layer B from the side where the resin material layer J is present (for example, heat input by thermal conduction from the magnetic material layer E), is converted into infrared light IR by the resin material layer J and radiated, thereby cooling the magnetic material layer E (more specifically, the side of the magnetic material layer E opposite the side where the cooling layer CP is present).
[0064] In other words, the cooling layer CP is configured to reflect the light L irradiated to the cooling layer CP, and also to radiate heat transferred to the cooling layer CP (e.g., heat transferred from the atmosphere or heat transferred from the magnetic material layer E) to the outside as infrared light IR. Furthermore, the resin material layer J, the protective layer D and the light reflecting layer B are flexible, so that the cooling layer CP (radiative cooling film) is configured to be flexible.
[0065] The magnetic material layer E includes ferrite as a magnetic material and a binder resin. The thickness of the magnetic material layer E is, for example, about 0.2 mm to 2.0 mm. Specifically, the magnetic material layer E is a magnet sheet that is formed by mixing crushed ferrite and a binder resin, forming the mixture into a sheet, and then magnetizing the mixture.
[0066] [Outline of resin material layer] The light absorptivity and emissivity (light emissivity) of the resin material forming the resin material layer J change depending on the thickness. Therefore, it is necessary to adjust the thickness of the resin material layer J so that it absorbs as little sunlight as possible and emits large thermal radiation in the so-called atmospheric window wavelength band (wavelength band from 8 μm to 14 μm).
[0067] Specifically, in terms of the light absorptance of sunlight, the thickness of the resin material layer J needs to be adjusted to a thickness such that the wavelength average of the light absorptance from wavelengths of 0.4 μm to 0.5 μm is 13% or less, the wavelength average of the light absorptance from wavelengths of 0.5 μm to 0.8 μm is 4% or less, the wavelength average of the light absorptance from wavelengths of 0.8 μm to 1.5 μm is within 1%, the wavelength average of the light absorptance from wavelengths of 1.5 μm to 2.5 μm is 40% or less, and the wavelength average of the light absorptance from wavelengths of 2.5 μm to 4 μm is 100% or less. In the case of such an absorptance distribution, the light absorptance of sunlight is 10% or less, which corresponds to 100 W or less in terms of energy.
[0068] As described later, the light absorption rate of the resin material increases as the thickness of the resin material increases. When the resin material is made thick, the emissivity of the atmospheric window becomes almost 1, and the thermal radiation emitted into space is 125 W / m 2 from 160 W / m 2 The solar light absorption in the protective layer D and the light reflecting layer B is 50 W / m 2 The sum of the solar light absorption in the resin material layer J, the protective layer D and the light reflecting layer B is 150 W / m 2 The temperature is below 100° C., and cooling proceeds if the atmospheric conditions are good. As described above, it is preferable to use a resin material that has a small light absorptance near the peak value of the solar spectrum for the resin material layer J.
[0069] Moreover, from the viewpoint of infrared radiation (thermal radiation), the thickness of the resin material layer J needs to be adjusted to a thickness such that the wavelength average of the emissivity in the wavelength range from 8 μm to 14 μm is 40% or more. 50W / m absorbed by protective layer D and light-reflecting layer B 2 In order to release about that amount of thermal energy of sunlight from the resin material layer J into space through thermal radiation from the resin material layer J, the resin material layer J needs to emit more thermal radiation than that amount. For example, when the outside temperature is 30°C, the maximum thermal radiation of the 8μm to 14μm atmospheric window is 200W / m 2(Calculated with an emissivity of 1). This value can be obtained on a clear day in a dry environment with thin air, such as a high mountain. Since the atmosphere is thicker in lowlands than in high mountains, the wavelength band of the atmospheric window is narrower and the transmittance is lower. Incidentally, this is called the "atmospheric window becoming narrower."
[0070] In addition, the environment in which the cooling layer CP (radiative cooling film) is actually used may be humid, and in that case the atmospheric window will be narrow. When used in low altitudes, the thermal radiation generated in the atmospheric window area is 160 W / m at 30°C under good conditions. 2 (calculated with emissivity of 1). When there is haze or smog in the sky, which is common in Japan, the atmospheric window becomes even narrower, and radiation into space is estimated at 125 W / m 2 It will be about that amount. In consideration of this situation, the wavelength average of the emissivity from 8 μm to 14 μm is set to 40% or more (thermal radiation intensity in the atmospheric window band is 50 W / m 2 ) it cannot be used in low altitude areas of the mid-latitudes.
[0071] Therefore, by adjusting the thickness of the resin material layer J so that it falls within the optically specified range taking into account the above factors, the heat output from the atmospheric window becomes greater than the heat input due to absorption of sunlight, making it possible to achieve radiative cooling outdoors even in a solar radiation environment. In this embodiment, the thickness of the vinyl chloride resin or vinylidene chloride resin forming the resin material layer J is 100 μm or less and 10 μm or more.
[0072] [Details of resin material] According to Kirchhoff's law, emissivity (ε) and light absorptance (A) are equal. Light absorptance can be calculated from the absorption coefficient (α) using the relation A=1-exp(-αt) (hereafter referred to as the light absorptance relation). Here, t is the film thickness. In other words, by adjusting the film thickness of the resin material layer J, a large thermal radiation can be obtained in a wavelength band with a large absorption coefficient. When performing radiative cooling outdoors, it is recommended to use a material with a large absorption coefficient in the wavelength band of the atmospheric window, that is, from 8 μm to 14 μm. In addition, to suppress the absorption of sunlight, it is advisable to use a material that has no or has a small absorption coefficient in the wavelength range of 0.3 μm to 4 μm, especially in the range of 0.4 μm to 2.5 μm. As can be seen from the relational equation between the absorption coefficient and the absorptance, the light absorptance (emissivity) changes depending on the film thickness of the resin material.
[0073] In order to lower the temperature below the surrounding atmosphere by radiative cooling in a solar radiation environment, if a material is selected that has a large absorption coefficient in the wavelength band of the atmospheric window and almost no absorption coefficient in the wavelength band of sunlight, then by adjusting the film thickness, it will absorb almost no sunlight but emit a lot of thermal radiation from the atmospheric window, meaning it is possible to create a state in which the output from radiative cooling is greater than the input of sunlight.
[0074] The solar spectrum only contains wavelengths longer than 0.295 μm. Note that ultraviolet rays are defined as the range of wavelengths shorter than 0.4 μm, visible light is defined as the range of wavelengths from 0.4 μm to 0.8 μm, near infrared rays are defined as the range of wavelengths from 0.8 μm to 3 μm, mid infrared rays are defined as the range of wavelengths from 3 μm to 8 μm, and far infrared rays are defined as the range of wavelengths longer than 8 μm.
[0075] Regarding the carbon-chlorine bond (C-Cl), the bond energy between the carbon and chlorine in an alkene is 3.28 eV, and the wavelength is 0.378 μm, so it absorbs a lot of ultraviolet light in sunlight, but has almost no absorption in the visible range. Figure 2 shows the absorption spectrum of a 100 μm thick polyvinyl chloride resin in the ultraviolet to visible range, and shows that optical absorption is high at wavelengths shorter than 0.38 μm. FIG. 2 shows the absorptance spectrum from ultraviolet to visible light for a 100 μm thick polyvinylidene chloride resin, and shows a slight increase in the absorptance spectrum on the shorter wavelength side than 0.4 μm.
[0076] Incidentally, FIG. 2 also shows the absorption spectrum from ultraviolet to visible range of ethylene terephthalate resin with a thickness of 40 μm, and the absorption spectrum from ultraviolet to visible range of ethylene resin.
[0077] Figure 3 shows the emissivity of polyvinyl chloride resin (PVC) with carbon-chlorine bonds at the atmospheric window, and Figure 4 shows the emissivity of polyvinylidene chloride resin (PVDC) with carbon-chlorine bonds at the atmospheric window. For carbon-chlorine bonds, the absorption coefficient due to the C-Cl stretching vibration appears in a broad band with a half-width of 1 μm or more centered at a wavelength of 12 μm. In the case of polyvinyl chloride resin, the absorption coefficient due to the bending vibration of CH of the alkene contained in the main chain appears at a wavelength of around 10 μm due to the electron-withdrawing effect of chlorine. The same is true for vinylidene chloride resin. Due to these effects, the wavelength average of the emissivity of a 10 μm thick film is 43% at wavelengths from 8 μm to 14 μm, which falls within the regulation of a wavelength average of 40% or more. As shown in the figure, the emissivity in the atmospheric window region increases as the film thickness increases.
[0078] As shown in Figure 3, in the case of polyvinyl chloride resin, even if the thickness exceeds 100 μm, there is almost no increase in thermal radiation in the atmospheric window region. In other words, in the case of polyvinyl chloride resin, thermal radiation in the atmospheric window occurs within a depth of about 100 μm from the surface, and radiation from deeper parts does not escape to the outside. As shown in FIG. 4, it can be seen that vinylidene chloride resin is similar to vinyl chloride resin.
[0079] As described above, the thermal radiation from the atmospheric window region generated from the surface of the resin material occurs within a depth of approximately 100 μm from the surface. If the resin thickness increases beyond this, the cold generated by radiation cooling of the cooling layer CP is insulated by the resin material that does not contribute to thermal radiation. Consider a case where a resin material layer J that ideally does not absorb any sunlight is fabricated on a light reflecting layer B. In this case, sunlight is absorbed only by the light reflecting layer B of the cooling layer CP. The thermal conductivity of resin materials is generally about 0.2 W / m / K. When calculations are made taking this thermal conductivity into account, if the thickness of the resin material layer J exceeds 20 mm, the temperature of the cooling surface (the surface of the light-reflecting layer B opposite the side where the resin material layer J is present) will rise.
[0080] Even if an ideal resin material that does not absorb any sunlight exists, the thermal conductivity of resin materials is generally around 0.2 W / m / K. Therefore, if the thickness exceeds 20 mm, the light-reflecting layer B will be heated by sunlight, and the magnetic material layer E placed on the light-reflecting layer side will also be heated. In other words, the thickness of the resin material of the cooling layer CP must be 20 mm or less.
[0081] [Thickness of resin material layer] From the viewpoint of practical use of the cooling layer CP, it is preferable that the thickness of the resin material layer J is thin. The thermal conductivity of resin materials is generally lower than that of metals, glass, etc. In order to effectively cool the magnetic material layer E, it is preferable that the thickness of the resin material layer J is the minimum necessary. The thicker the resin material layer J is, the greater the thermal radiation of the air window becomes, and above a certain thickness, the thermal radiation energy at the air window becomes saturated.
[0082] The film thickness at which the film saturates depends on the resin material, but in the case of a resin containing carbon-chlorine bonds, the film is saturated even at a thickness of 100 μm, and sufficient heat radiation can be obtained in the atmospheric window region even at a thickness of 50 μm. The thinner the resin material, the higher the thermal conductivity and the more effectively the temperature of the magnetic material layer E can be lowered, so in the case of a resin containing carbon-chlorine bonds, a thickness of 50 μm or less reduces the heat insulation and allows the magnetic material layer E to be effectively cooled. In the case of carbon-chlorine bonds, a thickness of 100 μm or less allows the magnetic material layer E to be effectively cooled.
[0083] The benefit of making the material thinner is not just that it reduces heat insulation and makes it easier to transfer cold. It also reduces the absorption of near-infrared light from CH, CH2, and CH3, which are caused by resins containing carbon-chlorine bonds. By making the material thinner, the amount of sunlight absorbed by these compounds can be reduced, which increases the cooling capacity of the cooling layer CP. From the above viewpoints, in the case of polyvinyl chloride resin and vinylidene chloride resin, which are resins containing carbon-chlorine bonds, a thickness of 50 μm or less can produce a more effective radiative cooling effect under sunlight.
[0084] [Details of the light reflecting layer] In order to provide the light reflecting layer B with the above-mentioned reflectance characteristics, the reflective material on the side where the emitting surface H exists (the side where the resin material layer J exists) needs to be silver or a silver alloy. As shown in FIG. 5, if the light-reflecting layer B is formed based on silver, the desired reflectance of the light-reflecting layer B can be obtained.
[0085] When reflecting sunlight using only silver or a silver alloy while maintaining the above-mentioned reflectance characteristics, a thickness of 50 nm or more is required. However, in order to provide flexibility to the light reflecting layer B, the thickness must be 100 μm or less. If it is thicker than this, it becomes difficult to bend. Incidentally, the "silver alloy" may be an alloy in which, for example, 0.4% to 4.5% by mass of any of copper, palladium, gold, zinc, tin, magnesium, nickel, and titanium is added to silver. A specific example is "APC-TR (made by Furuya Metal)," a silver alloy made by adding copper and palladium to silver.
[0086] In order to provide the light reflecting layer B with the above-mentioned reflectance characteristics, a structure may be used in which silver or a silver alloy is located adjacent to the protective layer D and aluminum or an aluminum alloy is located away from the protective layer D. Even in this case, the reflective material on the side where the emitting surface H exists (the side where the resin material layer J exists) needs to be silver or a silver alloy. When it is composed of two layers of silver (silver alloy) and aluminum (aluminum alloy), the thickness of the silver needs to be 10 nm or more, and the thickness of the aluminum needs to be 30 nm or more. However, in order to provide flexibility to the light reflective layer B, the total thickness of the silver and aluminum must be 100 μm or less. If it is thicker than this, it becomes difficult to bend.
[0087] Incidentally, examples of "aluminum alloys" that can be used include alloys in which aluminum has been doped with copper, manganese, silicon, magnesium, zinc, carbon steel for mechanical structures, yttrium, lanthanum, gadolinium, and terbium.
[0088] Silver and silver alloys are vulnerable to rain and humidity and need to be protected from them, and also need to be prevented from tarnishing. For this reason, a protective layer D is required to protect the silver, in a form adjacent to the silver or silver alloy, as shown in Figures 6 to 9. The protective layer D will be described in detail later.
[0089] [Specific configuration of composite cooling material] Since the resin material forming the resin material layer J and the protective layer D of the cooling layer CP is flexible, when the light reflecting layer B is made thin, the light reflecting layer B can also be made flexible, and as a result, the cooling layer CP can be made into a flexible film (radiative cooling film).
[0090] As shown in Figs. 6 to 9, the cooling layer CP (radiative cooling film) is attached to the outer surface of the magnetic material layer E with a connecting layer S of adhesive or pressure sensitive adhesive, thereby cooling the magnetic material layer E. The adhesive or pressure sensitive adhesive used in the connection layer S includes one or more of vinyl chloride resin, vinylidene chloride resin, polyolefin resin, polyester resin, acrylic resin, urethane resin, silicone resin, and rubber resin. Preferably, the connection layer S includes at least one of vinyl chloride resin and polyolefin resin.
[0091] There are various possible forms for producing the cooling layer CP in the form of a film. For example, it is possible to produce it by applying a protective layer D and a resin material layer J to a light reflecting layer B produced in the form of a film. Alternatively, it is possible to produce it by attaching a protective layer D and a resin material layer J to a light reflecting layer B produced in the form of a film. Alternatively, it is possible to produce it by applying or attaching a protective layer D on a resin material layer J produced in the form of a film, and then produce a light reflecting layer B on the protective layer D by deposition, sputtering, ion plating, silver mirror reaction, or the like.
[0092] Specifically, the cooling layer CP (radiative cooling film) in Fig. 6 is formed by forming a protective layer D on the upper side of the light reflecting layer B when the light reflecting layer B is formed as a single layer of silver or silver alloy, or when the light reflecting layer B is composed of two layers of silver (silver alloy) and aluminum (aluminum alloy), and forming a resin material layer J on the protective layer D, and also forming a lower protective layer Ds on the lower side of the light reflecting layer B. Incidentally, the lower protective layer Ds is formed of, for example, acrylic resin.
[0093] The cooling layer CP (radiative cooling film) in FIG. 6 can be produced by successively applying a protective layer D, a light-reflecting layer B, and a lower protective layer Ds onto a film-like resin material layer J, and molding them integrally.
[0094] The cooling layer CP (radiative cooling film) in FIG. 7 is configured such that the light-reflecting layer B is composed of an aluminum layer B1 formed of aluminum foil that functions as aluminum (aluminum alloy) and a silver layer B2 made of silver or a silver alloy, a protective layer D is formed on the upper side of the light-reflecting layer B, and a resin material layer J is formed on the upper part of the protective layer D.
[0095] The cooling layer CP (radiative cooling film) in FIG. 7 can be fabricated by sequentially applying a silver layer B2, a protective layer D, and a resin material layer J onto an aluminum layer B1 made of aluminum foil, and molding them together. As another manufacturing method, a method can be adopted in which the resin material layer J is formed into a film, a protective layer D and a silver layer B2 are successively applied onto the film-like resin material layer J, and an aluminum layer B1 is attached to the silver layer B2.
[0096] The cooling layer CP (radiative cooling film) in Figure 8 is configured such that the light-reflecting layer B is formed as a single layer of silver or silver alloy, or is composed of two layers of silver (silver alloy) and aluminum (aluminum alloy), a protective layer D is formed on the upper side of the light-reflecting layer B, a resin material layer J is formed on the upper part of the protective layer D, and a film layer F such as PET is formed on the lower side of the light-reflecting layer B.
[0097] The cooling layer CP (radiative cooling film) in Figure 8 can be produced by sequentially coating a light-reflecting layer B and a protective layer D on a film layer F (corresponding to the substrate) formed into a film shape using PET (ethylene terephthalate resin) or the like, forming them into an integrated body, and then adhering a separately formed film-shaped resin material layer J to the protective layer D with an adhesive layer N. The adhesive (pressure-sensitive adhesive) used in the glue layer N may be, for example, a urethane-based adhesive (pressure-sensitive adhesive), an acrylic-based adhesive (pressure-sensitive adhesive), or an EVA (ethylene vinyl acetate)-based adhesive (pressure-sensitive adhesive), and it is desirable for it to be one that has high transparency to sunlight.
[0098] The cooling layer CP (radiative cooling film) in Fig. 9 is configured such that the light-reflecting layer B is composed of an aluminum layer B1 functioning as aluminum (aluminum alloy) and a silver layer B2 made of silver or a silver alloy (silver substitute), the aluminum layer B1 is formed on the top of a film layer F (corresponding to the substrate) formed in a film shape from PET (ethylene terephthalate resin) or the like, a protective layer D is formed on the top of the silver layer B2, and a resin material layer J is formed on the top of the protective layer D.
[0099] The cooling layer CP (radiative cooling film) in Fig. 9 can be fabricated by applying an aluminum layer B1 onto a film layer F to integrally form the film layer F and the aluminum layer B1, and then applying a protective layer D and a silver layer B2 onto a film-like resin material layer J to integrally form the resin material layer J, the protective layer D and the silver layer B2, and then bonding the aluminum layer B1 and the silver layer B2 with a glue layer N. The adhesive (pressure-sensitive adhesive) used in the glue layer N may be, for example, a urethane-based adhesive (pressure-sensitive adhesive), an acrylic-based adhesive (pressure-sensitive adhesive), or an EVA (ethylene vinyl acetate)-based adhesive (pressure-sensitive adhesive), and it is desirable for it to be one that has high transparency to sunlight.
[0100] [Details of protective layer] The protective layer D is made of a polyolefin resin having a thickness of 300 nm or more and 40 μm or less, or a polyethylene terephthalate having a thickness of 17 μm or more and 40 μm or less. Polyolefin resins include polyethylene and polypropylene.
[0101] As mentioned above, FIG. 2 shows the ultraviolet light absorptance of polyethylene. FIG. 10 shows the light transmittance of polyethylene, which is suitable as the synthetic resin for forming the protective layer D.
[0102] Since the cooling layer CP (radiative cooling film) exerts a radiative cooling effect not only at night but also in a solar radiation environment, in order for the light-reflecting layer B to maintain its light-reflecting function, it is necessary to protect the light-reflecting layer B with a protective layer D so that the silver of the light-reflecting layer B does not discolor in a solar radiation environment.
[0103] When protective layer D is formed from a polyolefin-based resin to have a thickness of 300 nm or more and 40 μm or less, polyolefin-based resin is a synthetic resin whose ultraviolet light absorptance is 10% or less over the entire ultraviolet wavelength range from 0.295 μm to 0.4 μm, and therefore protective layer D is less susceptible to deterioration due to absorption of ultraviolet light.
[0104] Furthermore, since the thickness of the polyolefin resin forming protective layer D is 300 nm or more, it effectively performs the blocking function of blocking radicals generated in resin material layer J from reaching the silver or silver alloy forming the light-reflecting layer, and also blocks moisture penetrating resin material layer J from reaching the silver or silver alloy forming light-reflecting layer B, thereby suppressing discoloration of the silver or silver alloy forming light-reflecting layer B.
[0105] Incidentally, the protective layer D made of a polyolefin resin will deteriorate as it absorbs ultraviolet rays, forming radicals on the surface side away from the light-reflecting layer B. However, since the thickness is 300 nm or more, the formed radicals will not reach the light-reflecting layer B. Even if the protective layer D deteriorates as radicals are formed, the rate of deterioration is slow due to the low absorption of ultraviolet rays, and therefore the above-mentioned blocking function will be maintained for a long period of time.
[0106] When protective layer D is formed from ethylene terephthalate resin to a thickness of 17 μm or more and 40 μm or less, ethylene terephthalate resin is a resin material that has a higher ultraviolet light absorption rate in the ultraviolet wavelength range of 0.295 μm to 0.4 μm than polyolefin resins. However, since the thickness is 17 μm or more, it can effectively perform blocking functions for a long period of time, such as blocking radicals generated in resin material layer J from reaching the silver or silver alloy that forms light reflecting layer B and blocking moisture that penetrates resin material layer J from reaching the silver or silver alloy that forms light reflecting layer B, thereby suppressing discoloration of the silver or silver alloy that forms light reflecting layer B.
[0107] In other words, protective layer D made of ethylene terephthalate resin will deteriorate as it absorbs ultraviolet rays, forming radicals on the surface side away from light reflecting layer B. However, since the thickness is 17 μm or more, the formed radicals will not reach light reflecting layer B. Furthermore, even if protective layer D deteriorates while forming radicals, since the thickness is 17 μm or more, the above-mentioned blocking function will be exhibited for a long period of time.
[0108] To explain further, the deterioration of ethylene terephthalate resin (PET) is caused by ultraviolet light cleaving the ester bonds between ethylene glycol and terephthalic acid to form radicals. This deterioration progresses from the surface of the ethylene terephthalate resin (PET) that is irradiated with ultraviolet light.
[0109] For example, when ethylene terephthalate resin (PET) is irradiated with ultraviolet rays with the strength in Osaka, the ester bonds of the ethylene terephthalate resin (PET) are cleaved by about 9 nm per day, starting from the irradiated surface. Because the ethylene terephthalate resin (PET) is sufficiently polymerized, the cleaved ethylene terephthalate resin (PET) on the surface does not attack the silver (silver alloy) of the light-reflecting layer B. However, when the cleaved end of the ethylene terephthalate resin (PET) reaches the silver (silver alloy) of the light-reflecting layer B, the silver (silver alloy) will discolor.
[0110] Therefore, in order for protective layer D to last for one year or more when used outdoors, a thickness of about 3 μm is required, calculated by multiplying 9 nm / day by 365 days. In order for the ethylene terephthalate resin (PET) of protective layer D to last for three years or more, a thickness of 10 μm or more is required. In order for it to last for five years or more, a thickness of 17 μm or more is required.
[0111] In addition, when the protective layer D is formed of a polyolefin resin and an ethylene terephthalate resin, the reason for determining the upper limit of the thickness is to prevent the protective layer D from exhibiting heat insulating properties that do not contribute to radiative cooling. In other words, the protective layer D exhibits heat insulating properties that do not contribute to radiative cooling as the thickness increases, so the upper limit of the thickness is determined to prevent the protective layer D from exhibiting heat insulating properties that do not contribute to radiative cooling while still exerting the function of protecting the light reflecting layer B.
[0112] In other words, if the protective layer D becomes thicker, there will be no disadvantage in terms of preventing coloring of the silver (silver alloy) in the light-reflecting layer B, but problems will arise in terms of radiative cooling. In other words, making the protective layer D thicker will increase the thermal insulation properties of the radiative cooling material. For example, a resin whose main component is polyethylene, which is an excellent synthetic resin for forming the protective layer D, has a low emissivity at the atmospheric window, as shown in Figure 14, so even if it is formed thickly, it does not contribute to radiative cooling. On the contrary, making it thicker increases the thermal insulation of the radiative cooling material. Next, as the thickness increases, absorption of near-infrared light originating from the vibration of the main chain increases, increasing the effect of increasing solar absorption. Due to these factors, it is disadvantageous for radiative cooling to have a thick protective layer D. From this viewpoint, the thickness of the protective layer D made of a polyolefin resin is preferably 5 μm or less, and more preferably 1 μm.
[0113] Incidentally, as shown in Figure 8, when a glue layer N is located between the resin material layer J and the protective layer D, radicals will also be generated from the glue layer N. However, if the thickness of the polyolefin resin forming the protective layer D is 300 nm or more and the thickness of the ethylene terephthalate resin forming the protective layer D is 17 μm or more, the radicals generated in the glue layer N can be prevented from reaching the light reflective layer B for a long period of time.
[0114] [Considerations on protective layer] In order to examine the difference in the way the protective layer D colored the silver, a sample was prepared in which the protective layer D was exposed and did not have the resin material layer J as the infrared emitting layer A, as shown in FIG. 11, and the coloring of the silver after being irradiated with simulated sunlight was examined. That is, as the protective layer D, samples were formed by applying two types of materials, a general acrylic resin that absorbs ultraviolet rays (for example, methyl methacrylate resin mixed with a benzotriazole-based ultraviolet absorber) and polyethylene, to a film layer F (corresponding to the substrate) containing silver as a light reflecting layer B using a bar coater, and the function of the protective layer D was examined. The thicknesses of the applied protective layers D were 10 μm and 1 μm, respectively. The film layer F (corresponding to the substrate) is formed into a film shape using PET (ethylene terephthalate resin) or the like.
[0115] As shown in FIG. 13, if protective layer D is made of an acrylic resin that absorbs ultraviolet rays well, the protective layer D is decomposed by ultraviolet rays to form radicals, and the silver immediately turns yellow and no longer functions as a cooling layer CP (it absorbs sunlight and, like general materials, its temperature rises when exposed to sunlight). The 600h line in the figure indicates the time when the product was subjected to a xenon weather test under the conditions of JIS standard 5600-7-7 (ultraviolet light energy is 60W / m 2 The reflectance spectrum after 600h (hours) of exposure to xenon weathering is shown in Fig. 1. The 0h line is the reflectance spectrum before the xenon weathering test.
[0116] As shown in Figure 12, when protective layer D is made of polyethylene with low ultraviolet light absorption, no decrease in reflectance is observed from the near infrared region to the visible region. In other words, resins whose main component is polyethylene (polyolefin resins) hardly absorb the ultraviolet light contained in sunlight that reaches the ground, and therefore do not easily form radicals even when exposed to sunlight, so coloring of the silver serving as light-reflecting layer B does not occur even when exposed to sunlight. The 600h line in the figure indicates the time when the product was subjected to a xenon weather test under the conditions of JIS standard 5600-7-7 (ultraviolet light energy is 60W / m 2 The reflectance spectrum after 600h (hours) of exposure to xenon weathering is shown in Fig. 1. The 0h line is the reflectance spectrum before the xenon weathering test.
[0117] The reason why the reflectance spectrum in this wavelength band is wavy is due to the Fabry-Perot resonance of the polyethylene layer. It can be seen that the resonance position is slightly different between the 0h line and the 600h line due to the change in the thickness of the polyethylene layer caused by the heat of the xenon weather test, but no significant decrease in reflectance in the ultraviolet-visible range due to the yellowing of silver is observed.
[0118] In addition, from the viewpoint of ultraviolet absorption, fluororesin-based materials can also be used as materials for forming the protective layer D. However, when actually formed as the protective layer D, they become discolored and deteriorate during the formation stage, and therefore cannot be used as materials for forming the protective layer D. Silicone can also be used as a material for forming the protective layer D from the viewpoint of UV absorption, but it has extremely poor adhesion to silver (silver alloys) and cannot be used as a material for forming the protective layer D.
[0119] [Regarding plasticizer contamination] When the resin material layer J is made of a vinyl chloride resin, it is preferable to mix a plasticizer into the vinyl chloride resin to improve flexibility. The plasticizer to be mixed into the polyvinyl chloride resin is any one of phthalates, aliphatic dibasic acids, and phosphates. The plasticizer is mixed in an amount of 1 part by weight or more and 200 parts by weight or less per 100 parts by weight of the vinyl chloride resin. From the viewpoint of processing, the amount of the plasticizer is preferably 100 parts by weight or less.
[0120] The aliphatic dibasic acid ester of the plasticizer may be composed of adipic acid esters, adipic acid ester copolymers, azelaic acid esters, azelaic acid ester copolymers, sebacic acid esters, sebacic acid ester copolymers, succinic acid esters, and succinic acid ester copolymers, either alone or in combination.
[0121] The aliphatic dibasic acid ester of the plasticizer is preferably an aliphatic dibasic acid and two molecules of a saturated aliphatic alcohol bonded together via an ester bond. The phthalate ester of the plasticizer is preferably an ester bond between phthalic acid and two molecules of a saturated aliphatic alcohol. The phosphate ester of the plasticizer may be a phosphate triester or an aromatic phosphate ester.
[0122] <Details on phthalate esters> The list of phthalate esters is as follows: Dimethyl phthalate (DMP), diethyl phthalate (DEP), dibutyl phthalate (DPP), di-2-ethylhexyl phthalate (DOP), diisononyl phthalate (DINP), diisodecyl phthalate (DIDP), diundecyl phthalate (DUP), ditridecyl phthalate (DTDP), bis(2-ethylhexyl) terephthalate (DOTP), bis(2-ethylhexyl) isophthalate (DOIP), etc.
[0123] <Details of Aliphatic Dibasic Acid Esters> The aliphatic dibasic acid esters are listed below. Dibutyl adipate (DBA), diisobutyl adipate (DIBA), di-2-ethylhexyl adipate (DOA), diisononyl adipate (DINA), diisodecyl adipate (DIDA), bis-2-ethylhexyl azelaate (DOZ), dibutyl sebacate (DBS), di-2-ethylhexyl sebacate (DOS), diisononyl sebacate (DINS), diethyl succinate (DESU), and the like. Also, an aliphatic polyester having a molecular weight of 400 to 4000 synthesized by copolymerization (polyesterification) of a dibasic acid such as adipic acid with a diol (difunctional alcohol or glycol).
[0124] <Phosphate triester> The phosphoric acid triesters are listed as follows: Trimethyl phosphate (TMP), triethyl phosphate (TEP), tributyl phosphate (TBP), tris(2-ethylhexyl) phosphate (TOP).
[0125] <Aromatic phosphate ester> The aromatic phosphate esters are listed as follows: Triphenyl phosphate (TPP), tricresyl phosphate (TCP), trixylenyl phosphate (TXP), tresyl diphenyl phosphate (CDP), 2-ethylhexyl diphenyl phosphate.
[0126] <Appropriate evaluation of plasticizers> Plasticizers for polyvinyl chloride resin include phthalates, aliphatic dibasic acid esters, phosphate triesters, aromatic phosphate esters, trimellitic acid esters, and epoxidized fatty acid esters. The following compounds were selected from these plasticizers, and 43 parts by weight of each plasticizer was mixed with 100 parts by weight of vinyl chloride and evaluated using a xenon weather test. The vinyl chloride resin was mixed with 0.5 parts by weight of each of a triazine-based ultraviolet absorber and a hindered amine-based light stabilizer per 100 parts by weight of vinyl chloride.
[0127] Representative phthalate esters include di-2-ethylhexyl phthalate (DOP) and diisodecyl phthalate (DIDP). Representative aliphatic dibasic acid esters include di-2-ethylhexyl adipate (DOA), butanediol adipate copolymer (average molecular weight about 1000), and diisononyl adipate (DINA). A representative phosphate triester is tributyl phosphate (TBP). Tricresyl phosphate (TCP) is a representative aromatic phosphate ester. A representative trimellitic acid ester is tri-2-ethylhexyl trimellitate (TOTM). Epoxidized soybean oil is a representative example of an epoxidized fatty acid ester.
[0128] The durability test was conducted using a xenon weather test for 1920 hours (equivalent to 4 years of actual exposure), and the durability was judged based on the results. Note that 487 hours is equivalent to 1 year of UV exposure. The conditions for the xenon weather test are as follows: UV intensity 180W / m 2 (wavelength 295-400nm). <Conditions without watering> BPT89℃, humidity 50%, 1 hour 42 minutes. <Conditions with watering> Temperature inside the tank: 38°C, humidity: 90%, 18 minutes.
[0129] The test results for 1920 hours are shown in Figure 15. Incidentally, although the experiment was carried out using polyvinyl chloride resin in this embodiment, the same results were obtained using polyvinylidene chloride resin. As a result of the above experiment, it became clear that durability was significantly reduced when trimellitic acid ester (TOTM) and epoxidized fatty acid ester (epoxidized soybean oil) were used as plasticizers. Note that epoxidized fatty acid turned brown after 1120 hours and the test could not be continued, so it is not shown in the figure.
[0130] In contrast, it was found that when phthalate esters, aliphatic dibasic acid esters, phosphate triesters, or aromatic phosphate esters are used as plasticizers to be mixed into the polyvinyl chloride resin, the reflectance of the cooling layer CP does not decrease even after about four years have passed, but when trimellitate esters or epoxidized fatty acid esters are used as plasticizers to be mixed into the polyvinyl chloride resin, the reflectance of the cooling layer CP decreases significantly even before about four years have passed.
[0131] The above test results show that, as plasticizers for polyvinyl chloride resins, phthalate esters, aliphatic dibasic acid esters, phosphate triesters, and aromatic phosphate esters have excellent durability, while trimellitate esters and epoxidized fatty acid esters have no durability. The reasons for this will be considered and systematized as described below.
[0132] [Other additives] The vinyl chloride resin forming the resin material layer J may contain a flame retardant, a stabilizer, a stabilizing aid, a filler, an antioxidant, an ultraviolet absorbing agent, and a light stabilizer.
[0133] [Another configuration of the cooling layer] As shown in Figure 16, the cooling layer CP may be configured to have an anchor layer G on top of a film layer F (corresponding to the substrate), and a light-reflecting layer B, a protective layer D, and an infrared-emitting layer A on top of the anchor layer G. The film layer F (corresponding to the substrate) is formed into a film shape using, for example, PET (ethylene terephthalate resin) or the like.
[0134] The anchor layer is introduced to strengthen the adhesion between the film layer F and the light-reflecting layer B. In other words, if one were to form a film of silver (Ag) directly on the film layer F, there is a risk that it would easily peel off. The anchor layer G is preferably made primarily of acrylic, polyolefin, or urethane, with a mixture of a compound with an isocyanate group or melamine resin. As it is a coating for parts that are not directly exposed to sunlight, it is acceptable for it to be made of a material that absorbs ultraviolet rays. There are other methods for strengthening the adhesion between the film layer F and the light reflecting layer B than inserting the anchor layer G. For example, the adhesion can be increased by roughening the surface of the film layer F by irradiating the surface with plasma.
[0135] [Considerations on connection layers] The magnetic material layer E and the cooling layer CP are connected to each other by a connection layer S between the magnetic material layer E and the cooling layer CP, the connection layer S including at least one of vinyl chloride resin, vinylidene chloride resin, polyolefin resin, acrylic resin, urethane resin, silicone resin, and rubber resin. More preferably, the connection layer S includes at least vinyl chloride resin and polyolefin resin.
[0136] The thickness of the magnetic material layer E is preferably about 0.2 mm or more and 2.0 mm or less. As shown in the following [Table 1], by making the thickness 0.2 mm or more, the magnetic force acting as the attachment force to the metallic plate-like body to be attached can be exhibited well, and long-term adhesion stability can be improved. In addition, by making the thickness 2.0 mm or less, even if there is a heat source on the back side (opposite side to the side where the cooling layer CP exists) of the composite cooling material W, the heat dissipation from the back side (opposite side to the side where the cooling layer CP exists) to the outer side (side where the cooling layer CP exists) can be maintained at a certain level or more. [Table 1]
[0137] Table 2 shows the test results comparing the peeling and reusability of the magnetic material, the temperature difference between the temperature on the back side and the air temperature on the outer side, and the thermal conductivity from the back side to the cooling layer CP with other materials. In this test, SPACECOOL Film SCF-A25M-ONS manufactured by SPACECOOL was used as a film with adhesive as another material for comparison, and SPACECOOL-200E manufactured by SPACECOOL was used as a membrane material. The test showed that the peelability and reusability of the magnetic material was comparable to that of the film material, but higher than that of the adhesive film. As for thermal conductivity, the film showed high thermal conductivity, similar to that of the adhesive film, and higher than that of the film material in which an air layer is formed. [Table 2]
[0138] As shown in FIG. 17, the composite cooling material W may have a cooling layer CP with a radiation surface H formed in an uneven shape. That is, for example, the radiation surface H may be formed in such a manner that a convex portion U exists. Specific examples of unevenness include a line-and-space structure in which rectangular parallelepiped protrusions U are lined up (see Figure 18), a structure in which conical prism-shaped protrusions U are lined up vertically and horizontally (see Figure 19), a structure in which triangular prism or pyramid-shaped protrusions U are lined up in a line-and-space pattern (not shown), a structure in which rectangular shaped protrusions U are lined up vertically and horizontally, and a structure in which protrusions U are formed randomly. Incidentally, when forming the radiation surface H in an uneven shape, the height difference is about 100 μm.
[0139] When the radiation surface H is formed in an uneven shape, if there is heat inflow from various heat sources to the inside of the magnetic material layer E of the composite cooling material W (the side opposite to the side where the cooling layer CP is present), the temperature is likely to rise above the environmental temperature (outside air temperature) during the day, even though the cooling layer CP is provided. When the temperature inside the magnetic material layer E of the composite cooling material W is higher than the environmental temperature (outside air temperature), the outside air acts as a cold heat source, and it is desirable to increase the heat exchange with the outside air. From this perspective, it is preferable to form the radiation surface H of the composite cooling material W in an uneven shape to increase the surface area, and to increase the heat exchange with the wind on the side of the radiation surface H of the composite cooling material W.
[0140] From this viewpoint, as shown in FIG. 17, it is advisable to form the infrared radiating layer A of the cooling layer CP in an uneven shape by embossing or the like to increase the surface area. In other words, this structure is suitable for use when there is a heat source other than sunlight or heated air, the temperature of the magnetic material layer E on which the cooling layer CP is attached rises above the environmental temperature (outside air temperature), and the environmental temperature (outside air temperature) acts as cold heat.
[0141] Forming the radiation surface H in an uneven shape also has an advantage in terms of appearance. When the radiation surface H (upper surface) of the cooling layer CP is formed in an uneven shape, sunlight is scattered more than when it is a mirror surface, so glare on the cooling layer CP is reduced. A less glarey cooling layer CP improves visibility, and therefore increases safety when driving. Incidentally, even if the radiation surface H is endowed with the function of "scattering," the light absorption in the silver (silver alloy) of the light reflecting layer B does not increase, and therefore radiation cooling can be performed satisfactorily.
[0142] [Another configuration of the cooling layer] As shown in Figures 20 and 21, the resin material layer J constituting the infrared radiation layer A may be provided with a plurality of granular light reflecting portions Q that reflect light. The light reflecting portions Q are composed of air bubbles Qa, inorganic filler Qb, and organic filler Qc. The particle size of the light reflecting portions Q is 1 nm or more and 300 μm or less, and more preferably 10 nm or more and 100 μm or less, from the viewpoint of dispersibility and cohesiveness. The particle size of the light reflecting portions Q can be suitably set to the "average particle size" specified by JIS. The method for forming the light reflecting portion Q in the resin material layer J includes, for example, calendar molding of a compound resin in which the light reflecting portion Q and a resin serving as a binder are kneaded, but is not limited to this. The proportion of the light reflecting portion Q in the resin material layer J is preferably about 0.01 volume % or more and 20 volume % or less. The light reflecting portion Q is porous.
[0143] The inorganic filler Qb includes at least one of glass microbeads, ceramic microbeads, silicon oxide particles, silicon carbide particles, silicon nitride particles, barium sulfate particles, and calcium carbonate particles. The organic filler Qc also contains at least one type of polymer having any one of the functional groups CO, C-Cl, CF, CN, C-Si, and Si-O.
[0144] In this way, by providing the light reflecting portion Q in the resin material layer J, in addition to the function of radiative cooling, the resin material layer J can exhibit the function of solar radiation reflection. When the solar radiation reflection function of the light reflecting portion Q is sufficiently high, the light reflecting layer B is omitted.
[0145] Furthermore, as shown in Figures 22 and 23, when a glue layer N connecting the resin material layer J and the protective layer D is provided between the resin material layer J and the protective layer D, the light reflecting portion Q may be formed in the glue layer N. The adhesive or pressure sensitive adhesive used in the paste layer may be a urethane-based, acrylic-based, ethylene vinyl acetate-based, or the like. In other words, the adhesive (pressure-sensitive adhesive) used in the glue layer N may be, for example, a urethane-based adhesive (pressure-sensitive adhesive), an acrylic-based adhesive (pressure-sensitive adhesive), an EVA (ethylene vinyl acetate)-based adhesive (pressure-sensitive adhesive), etc., and one that has high transparency to sunlight is applied. Incidentally, the thickness of the glue layer N is, for example, about 10 μm.
[0146] Incidentally, the composite cooling material W shown in Figures 20 to 23 has a configuration equivalent to that of the composite cooling material W shown in Figure 8, but when the light reflecting portion Q is formed in the resin material layer J, the composite cooling material W having the configuration shown in Figures 6, 7, and 9 can be applied.
[0147] By forming the light reflecting portion Q in the resin material layer J, when the cooling layer CP is viewed from the side where the radiation surface H exists, the light reflecting portion Q formed in the transparent resin material layer J is seen. Therefore, due to the light scattering effect of the light reflecting portion Q, the color of the composite cooling material W when viewed from the side where the radiation surface H exists appears white, thereby improving the aesthetic appearance.
[0148] In addition, since a light reflecting portion Q is formed in the glue layer N connecting the resin material layer J and the protective layer D, when the cooling layer CP is viewed from the side where the radiation surface H exists, the light reflecting portion Q mixed into the glue layer N can be seen through the transparent resin material layer J. Therefore, due to the light scattering effect of the light reflecting portion Q, the color of the composite cooling material W when viewed from the side where the radiation surface H exists becomes white, thereby improving the aesthetic appearance. The light reflecting portion Q may be formed on both the resin material layer J and the glue layer N.
[0149] Incidentally, when the light reflecting portion Q is formed in the resin material layer J by using the inorganic filler Qb or the organic filler Qc, both the front and back surfaces of the resin material layer J become uneven. When the back surface of the resin material layer J is uneven, it is desirable to position the adhesive layer N between the resin material layer J and the protective layer D. In other words, even if the back surface of the resin material layer J is uneven, the adhesive layer N (bonding layer) is located between the resin material layer J and the protective layer D, so that the resin material layer J and the protective layer D can be bonded appropriately. In addition, when the back surface of the resin material layer J is uneven, the resin material layer J and the protective layer D may be directly bonded by, for example, plasma bonding. Note that the plasma bonding is a form in which radicals are formed on the bonding surface of the resin material layer J and the bonding surface of the protective layer D by emitting plasma, and bonding is performed by the radicals.
[0150] [Regarding filler contamination in the protective layer] Incidentally, when a filler (at least one of inorganic and organic fillers) is mixed into the protective layer D, the back surface of the protective layer D in contact with the light reflecting layer B becomes uneven, which causes the surface of the light reflecting layer B to deform into an uneven shape, and therefore it is necessary to avoid mixing a filler into the protective layer D. In other words, if the surface of the light reflecting layer B deforms into an uneven shape, it will not be possible to properly reflect light, and as a result, it will not be possible to properly perform radiative cooling.
[0151] The experimental results regarding this point will be explained with reference to FIG. In Figure 24, "forming an Ag layer directly on the light diffusion layer" means forming a light reflecting layer B by mixing filler or depositing a silver (Ag) film by vapor deposition or the like on the surface of the infrared radiation layer A (resin material layer J) which has embossed irregularities on the Ag layer side which is the light reflecting layer B. In addition, "a light diffusion layer on a mirror-like Ag surface" means that the upper surface of the Ag layer, which is the light-reflecting layer B, is formed in a mirror-like shape, and on top of the Ag layer, a protective layer D, and an infrared-emitting layer A (resin material layer J) containing filler or having an embossed uneven surface are laminated.
[0152] As shown in Figure 24, in the case of "forming an Ag layer directly on the light diffusion layer," the surface of light-reflecting layer B becomes uneven, resulting in a significant drop in light reflectance. However, in the case of "light-diffusing layer on mirror-like Ag," the surface of light-reflecting layer B is maintained in a mirror-like state, and appropriate light reflectance is obtained.
[0153] [Another configuration of the infrared radiation layer] As shown in FIG. 25, both the front and back surfaces of a resin material layer J constituting an infrared emitting layer A may be formed in an uneven shape to provide a light scattering structure. With this configuration, glare from the emitting surface H when the emitting surface H is viewed can be suppressed.
[0154] In other words, the resin material layer J of the cooling layer CP shown in Figures 6 to 9 is flat on both the front and back sides and is configured so as not to include any light-reflecting portions Q. In such a configuration, the radiating surface H becomes mirror-like, and so glare is perceived when looking at the radiating surface H. However, by providing the light-reflecting portions Q, this glare can be suppressed.
[0155] The front and back surfaces of the resin material layer J can be made uneven by embossing or scratching the surface. Even if the rear surface of the resin material layer J is uneven, by positioning the adhesive layer N between the resin material layer J and the protective layer D, the resin material layer J and the protective layer D can be appropriately bonded to each other.
[0156] [Another embodiment] Other embodiments are listed below. (1) In the above embodiment, the protective layer D is provided, but the protective layer D may be omitted.
[0157] (2) In the above embodiment, the cooling layer CP has the first optical characteristic of a solar reflectance of 80% or more and the second optical characteristic of an average emissivity of 80% or more, which is the wavelength average of the emissivity of infrared light of 8 μm or more and 14 μm or less. However, the cooling layer CP is not limited to this configuration, and may have only the first optical characteristic. Moreover, the cooling layer CP may be configured such that the light reflecting portion Q is provided in the resin material layer J that does not have the second optical property, and the light reflecting layer B is not provided. Furthermore, the cooling layer CP may be composed of a resin material layer J that does not have the second optical property and a light reflecting layer B. In this case, the resin material layer J may or may not have a light reflecting portion Q.
[0158] (3) In the above embodiment, the resin material layer J constituting the infrared radiation layer A is provided with a plurality of granular light reflecting portions Q that reflect light. However, the light reflecting portions Q do not necessarily have to be provided. In addition, the light reflecting portions Q include air bubbles Qa, inorganic fillers Qb, and organic fillers Qc. However, the present invention is not limited to such a configuration, and the light reflecting portion Q may include at least one of air bubbles Qa, inorganic filler Qb, and organic filler Qc. Moreover, although the particle size of the light reflecting portion Q is 1 nm or more and 300 μm or less in the above example, the light reflecting portion Q may have a particle size other than this.
[0159] (4) The light reflecting portion Q may be formed using an inorganic material such as silicon dioxide (SiO2), titanium oxide (TiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), calcium carbonate (CaCO3), or the like. In particular, titanium oxide (TiO2) of about 200 nm, which has no photocatalytic activity, can be suitably used. In addition, titanium oxide (TiO2) may be coated with at least one of alumina, silica, and zirconia. By doing so, the light reflecting portion Q can be appropriately made to have no photocatalytic activity, which makes it easier to suppress deterioration of the resin material layer J.
[0160] In addition, the configurations disclosed in the above embodiments (including other embodiments, the same applies below) can be applied in combination with configurations disclosed in other embodiments, provided no contradiction arises. Furthermore, the embodiments disclosed in this specification are illustrative, and the embodiments of the present invention are not limited thereto, and can be appropriately modified within the scope that does not deviate from the purpose of the present invention. [Industrial Applicability]
[0161] INDUSTRIAL APPLICABILITY The composite cooling material of the present invention can be effectively used as it provides a composite cooling material that can improve usability. [Explanation of symbols]
[0162] A Infrared radiation layer B Light reflective layer E Magnetic material layer H radiation surface J Resin material layer Q Light reflective area Q2 Inorganic filler Q3 Organic filler
Claims
1. a magnetic material layer including a magnetic material; a cooling layer provided on an outer surface of the magnetic material layer; The cooling layer has a first optical property of having a solar reflectance of 80% or more.
2. the cooling layer is configured to include an infrared emitting layer that emits infrared light from a radiation surface, and a light reflecting layer located on the infrared emitting layer opposite to the side on which the radiation surface is present, and has a second optical characteristic in which an average emissivity, which is a wavelength average of the emissivity of infrared light of 8 μm or more and 14 μm or less, is 80% or more; the infrared radiation layer is a resin material layer made of a vinyl chloride resin or a vinylidene chloride resin and has a thickness adjusted to emit thermal radiation energy in a wavelength band of 8 μm to 14 μm that is greater than absorbed solar light energy, the light reflective layer comprises silver or a silver alloy; 2. The composite cooling material according to claim 1, wherein the cooling layer and the magnetic material layer are connected by a connecting layer containing one or more of vinyl chloride resin, vinylidene chloride resin, polyolefin resin, polyester resin, acrylic resin, urethane resin, silicone resin, and rubber resin.
3. The composite cooling material according to claim 1 or 2, wherein the connecting layer contains at least one of a polyvinyl chloride resin and a polyolefin resin.
4. 3. The composite cooling material according to claim 1, wherein the magnetic material layer contains at least ferrite and a binder resin, and has a thickness of 0.2 mm or more and 2.0 mm or less.
5. the cooling layer includes an infrared emitting layer that emits infrared light from an emitting surface; The composite cooling material according to claim 1 or 2, wherein the infrared radiation layer has a plurality of granular light reflecting portions that reflect light.
6. The composite cooling material according to claim 5 , wherein the particle size of the light reflecting portion is from 1 nm to 300 μm.
7. The composite cooling material according to claim 6, wherein the light reflecting portion is porous.
8. The light reflecting portion includes at least one of an inorganic filler and an organic filler, The inorganic filler includes at least one of glass microbeads, ceramic microbeads, silicon oxide particles, silicon carbide particles, silicon nitride particles, barium sulfate particles, and calcium carbonate particles; The composite cooling material according to claim 6, wherein the organic filler contains at least one polymer having any one of functional groups of C-O, C-Cl, C-F, C-N, C-Si, and Si-O.
9. The cooling layer includes an inorganic filler, 3. The composite cooling material according to claim 1, wherein the inorganic filler comprises at least one of glass microbeads, ceramic microbeads, silicon oxide particles, silicon carbide particles, silicon nitride particles, barium sulfate particles, and calcium carbonate particles.
10. The thickness of the resin material layer is The composite cooling material according to claim 2, wherein the thickness is adjusted to provide light absorption characteristics such that the wavelength average of the light absorptance at wavelengths of 0.4 μm to 0.5 μm is 13% or less, the wavelength average of the light absorptance at wavelengths of 0.5 μm to 0.8 μm is 4% or less, the wavelength average of the light absorptance at wavelengths of 0.8 μm to 1.5 μm is within 1%, and the wavelength average of the light absorptance at wavelengths of 1.5 μm to 2.5 μm is 40% or less.
11. 3. The composite cooling material according to claim 2, wherein the light reflective layer has a reflectance of 90% or more at wavelengths of 0.4 μm to 0.5 μm and a reflectance of 96% or more at wavelengths longer than 0.5 μm.
12. The composite cooling material according to claim 2 , wherein the light reflecting layer has a thickness of 50 nm or more.
13. 3. The composite cooling material according to claim 2, wherein the light reflecting layer has a laminated structure of silver or a silver alloy located closer to the resin material layer and aluminum or an aluminum alloy located away from the resin material layer.
Citation Information
Patent Citations
Method of manufacturing bonded magnet and rubber magnet
JP2005259761A
Back sheet for solar cell module
JP2014095066A
Radiation cooling type box
JP2021143795A
Apparatus and method for manufacturing float glass
JP2023064366A
Wall protection magnetic sheet
JP3227517U